Using of magnetic particles for fi xing of isolated cells in subretinal transplantation - A. A. Temnov; Yu. A. Belyy; S. A. Mirgorodskaya; A. D. Semenov; A. V. Shatskikh; A. V. Revishchin; G. V. Pavlova; N. N. Kust; A. N. Sklifas (Трансплантология (Москва))
Purpose: This study focuses on the development of the method of introduction of magnetic microparticles in the cytoplasm of HEK-293 cell line with their subsequent fixation under the retina of the eye.Materials and Methods. Magnetic particles (d = 2,8 mm) were treated with pluronic and injected into the cytoplasm of HEK-293 cell line, expressing GFP. The surgery was made under general anesthesia. HEK-293 containing magnetic particles were injected into the subretinal space of rabbit eyes (eyes 96, 48 rabbits) using original dosing device. In the experimental group (48 eyes, 24 rabbits) we fixed episcleral magnetic implant to hold cells in local place. In the control group (48 eyes, 24 rabbit) magnetic implant was not fixed. After the surgery all animals were examined using biomicroscopy, ophthalmoscopy with photographic recording, ultrasound, computed tomography and morphological study in certain terms (1, 3, 5, 7, 14, 21 day and 1 month).Results: The introduction of the magnetic particles into the cytoplasm of HEK 293 cell line has no effect on cell viability. HEK-293 containing magnetic particles remains in the place of injection during 21 days in rabbit eyes, where the magnetic implants were fixed (in control group during 3 days). Conclusions: Using of cells containing magnetic particles with fixation of the magnetic implant can be a promising method for cell therapy for the treatment of retinal diseases.